2000
DOI: 10.1002/1096-8628(20001127)95:3<241::aid-ajmg11>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome of gingival hypertrophy, hirsutism, mental retardation and brachymetacarpia in two sisters: Specific entity or variant of a described condition?

Abstract: Two sisters born to consanguineous Lebanese parents had mental retardation and epilepsy, brachymetacarpalia, hirsutism, bulbous soft nose, thick floppy ears with abnormal configuration and gingival hypertrophy. One girl presented additionally with tetralogy of Fallot and the other with congenital hypothyroidism and bilateral ureteral stenosis. These manifestations resemble the syndrome of hypertrichosis-gingival fibromatosis-mental retardation and seizures of Anavi et al. [1989: Dev Med Child Neurol 31:538-542… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Many patients who develop a certain syndrome have consanguineous parents. There is a wide spectrum of clinical and genetic heterogeneity, and patients who are members of the same family can exhibit different phenotypes as a result of a variable penetrance of HGF 9–17 . As suggested, chromosomes 2, 4, and 5 seem to include the most important and known genetic loci, including 2p21‐p22, 2p13‐p16, 5q13‐q22, 4q21, and 4q that enable mutations, duplications, deletions, and other genetic anomalies to take place.…”
Section: Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Many patients who develop a certain syndrome have consanguineous parents. There is a wide spectrum of clinical and genetic heterogeneity, and patients who are members of the same family can exhibit different phenotypes as a result of a variable penetrance of HGF 9–17 . As suggested, chromosomes 2, 4, and 5 seem to include the most important and known genetic loci, including 2p21‐p22, 2p13‐p16, 5q13‐q22, 4q21, and 4q that enable mutations, duplications, deletions, and other genetic anomalies to take place.…”
Section: Pathogenesismentioning
confidence: 99%
“…Other genetic loci, such as 8, 14q, 19p, 19q, and Xq, are also related to syndromes associated with HGF. Recent findings have been reported that a mutation in Son of sevenless‐1 (SOS‐1) is the most frequent genetic mechanism related to the isolated form of HGF 1,8,9,15 . SOS‐1 is a bifunctional guanine nucleotide factor that regulates the activity of Ras, Rac, and Rho proteins.…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Others have reported diabetes mellitus, vascular skin lesions and ocular abnormalities as part of Ramon syndrome [12,21,22]. Interestingly, the combination of epilepsy, mental retardation, hypertrichosis and GF are defined as idiopathic or HGF [8,18,19,[28][29][30][31]. Other phenotypic expressions like giant cell tumor and osteofibrosis are also known to occur in HGF [19].…”
Section: Discussionmentioning
confidence: 99%
“…This entity is characterized by mental retardation, epilepsy, brachymetacarpalia, hirsutism, bulbous short nose, thick floppy ears with abnormal configuration, and gingival hypertrophy. In addition, congenital cardiopathy and hypothyroidism are present (3, 41, 42).…”
Section: Generalized Hypertrichosesmentioning
confidence: 99%